Cockfighters in The Legal, Religious, and Social Perspectives - Ismail, Ismail (KARSA: Journal of Social and Islamic Culture, 2016)
This study examines the issues related to religious behavior in terms of religious beliefs, religious observance, motivation of doing cockfights, and social perception of cockfighters. From the data analysis found that: first, according to Islamic law, cockfighting is haram, while according to the positive law cockfighting accompanied by gambling is a crime. Secondly, according to their involvement, the cockfighters can be grouped into: tokang tanggha’, bhutto, and petaro (gamblers). Thirdly, in the context of belief, the cockfighters remain consistent in his religion (Islam). Fourth, religious observance for cockfighters is simply the practice of social worship. Fifth, is the motivation for cockfighters, among others, are friendship, art, gambling, prestige, and media of communication to solve the social problems. Sixth, the public perceives the actor of cockfighting as someone who still does not get guidance from Allah.Copyright (c) 2016 by KARSA. All right reserved DOI: 10.19105/karsa.v24i1.1010